2020
DOI: 10.1038/s41586-020-1947-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of adrenergic CaV1.2 stimulation revealed by proximity proteomics

Abstract: Increased cardiac contractility during fight-or-flight response is caused by β-adrenergic augmentation of Ca V 1.2 channels 1-4. In transgenic murine hearts expressing fully PKA phosphorylation-site-deficient mutant Ca V 1.2 α 1C and β subunits, this regulation persists, implying involvement of extra-channel factors. Here, we identify the mechanism by which β-adrenergic agonists stimulate voltage-gated Ca 2+ channels. We expressed α 1C or β 2B subunits conjugated to ascorbate-peroxidase 5 in mouse hearts and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
254
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 194 publications
(268 citation statements)
references
References 74 publications
13
254
0
1
Order By: Relevance
“…Furthermore, Hofmann's group recalculated Catterall's data and showed that in both groups' knock-in mice, the β-adrenergic stimulation for wild-type and mutant channels were equivalent [58]. This confirmed our initial findings [54], which we have further substantiated with additional transgenic mice [59,60].…”
Section: Additional Phosphorylation Sitessupporting
confidence: 77%
See 3 more Smart Citations
“…Furthermore, Hofmann's group recalculated Catterall's data and showed that in both groups' knock-in mice, the β-adrenergic stimulation for wild-type and mutant channels were equivalent [58]. This confirmed our initial findings [54], which we have further substantiated with additional transgenic mice [59,60].…”
Section: Additional Phosphorylation Sitessupporting
confidence: 77%
“…Finally, we crossed 35-mutant α 1C with 28-mutant β 2B transgenic mice. These mutant channels also displayed a normal isoproterenol-or forskolininduced increase in peak Ca 2+ current [59]. These results indicate that β-adrenergic stimulation of Ca V 1.2 does not involve direct phosphorylation of α 1C or β 2 subunits.…”
Section: Additional Phosphorylation Sitesmentioning
confidence: 69%
See 2 more Smart Citations
“…This inhibition is relieved by protein kinase A phosphorylation of Rad, and is the long sought‐after mechanism by which β‐adrenergic agonists increase cardiac Ca V 1.2 to enhance inotropy during the fight‐or‐flight response (Liu et al . 2020).…”
Section: Voltage‐gated Calcium Channels: Basic Structure Function Anmentioning
confidence: 99%